Solar Particle Radiation Storms Forecasting and Analysis (Springer Nature, 2021)
Solar Energetic Particles; Space Weather Forecasting; Solar Flares; Coronal Mass Ejections; Solar Wind Shock Waves; Particle Acceleration in the Solar Corona; Gamma-Ray Flares